Design Space Exploration for Mixed-Criticality Embedded Systems Considering Hypervisor-Based SW Partitions - Muttillo, Vittoriano; Valente, Giacomo; Pomante, Luigi (2018 21st Euromicro Conference on Digital System Design (DSD), 2018)
This work faces the role of Design Space Exploration for embedded systems based on heterogeneous parallel architectures and subject to mixed-criticality system requirements, while considering the exploitation of hypervisor-based SW partitions to better manage isolation. In particular, it presents an evolutionary partitioning and mapping approach integrated into a reference Electronic System Level HW/SW Co-Design framework to propose and early validate design solutions by means of HW/SW Co-Simulations.